COMPOSITES OF STARCHâMETHYL MYRISTATE COMPLEX AND POLY(VINYL ALCOHOL) FOR EDIBLE PLASTIC APPLICATIONS - Anisa, Santi
Cling wrap, a type of food packaging, is one of the most extensively used materials for food. The plastic is thin and easily sticks, making recycling challenging because it can choke the recycling engine. One solution to this challenge is to develop proper edible plastic packagings from natural polymers that are edible for humans. Starch is a polysaccharide commonly used in edible packaging films because it is abundant, food grade, edible, and biodegradable. In this research, plastics were produced from composite of starch–methyl myristate complexes and poly(vinyl alcohol) (PVA) (MM = 70,000 g/mol). Cassava starch (P) was isolated with a recovery of 5%(w/w) and amylose content of 19.4%. The inclusion complexes were made by mixing starch and methyl myristate at 90°C for 2 hours with varying concentrations of methyl myristate; 1, 3, 5, and 10% (w/w based on the total weight of the complexes). The starch–methyl myristate (PM) complexes were characterized by FTIR (Fourier-Transform Infrared Spectroscopy), XRD (X-Ray Powder Diffraction), TGA (Thermographymetry Analysis), solid and liquid DSC (Differential Scanning Calorimetry), PSA (Particle Size Analyzer), and UV-Vis spectrophotometer. Vibrations of the guest molecules on the FTIR spectra did not appear in the complexes, which indicated that methyl myristate molecule were already included inside the single helices of amylose molecules. The presence of diffraction peaks (2?) at 13 and 20° in the XRD diffractograms indicated that the amylose molecules in the complexes formed V6-amylose single helices. The DSC results of the PM complexes showed the presence of an endothermic peak belonging to the melting of complexes at 90–96 ºC (?H 1,1–3,3 J/g) and at 58 ºC (?H 0,2–0,4 J/g) belonging to the starch gelatinization. PSA and SEM results are difficult to observe due to the aggregation of sample. According to PSA, the diameter of the PM complexes were 29–162 nm. SEM characteriation showed that the particle size of native starch granules was 10 ?m. However, the particle size of the PM complexes were difficult to observe through SEM due to aggregation. The enzymatic degradation tests for 240 minutes showed that the hydrolysis of PM complex (66-71%) occurs slower than the native starch sample (75.5%). Poly(vinyl alcohol) and starch–methyl myristate dilm was made of PVA and PM-1%, PM-3%, PM-5%, and PM-10% complexes. The ratio of PVA:starch–methyl myristate complex of 1:3 (variant A), 1:1 (variation B), and 3:1 (variation C) on poly(vinyl alcohol) and starch–methyl myristate (PVPM) films. PVPM films were characterized by FTIR, mechanical test, soil burial test, and enzymatic degradation test. The mechanical strength test showed that (1) in general, the presence of 1-3% (b/b) methyl myristate in the starch complex increases the tensile strength and elongation of the film, (2) increasing the amount of PVA increased the tensile strength and maximum percent elongation of the film, and (3) the optimum mechanical strength considering the daily consumption limit was determined to be the PVPM-3% B, which had a ratio of PVA:PM-3% 1:1, with tensile strength of 9 MPa and percent elongation of 260%. Additionally, compared to PVPM films that utilized only one plasticizer, the tensile strength and maximum percent elongation of the films were improved when glycerol and citric acid were used as plasticizer and co-plasticizer on the PVPM films. The PVPM films decomposed more than 50% within 7 days after soil burial test on pH of 6.8–7.0 and relative humidity of 60–80%. During the 240-minute enzymatic degradation test, the FPM-3% complex film digested 8.7% slower than the pure starch (FP) film. The amount of starch hydrolyzed on the PVPM film also reduced as the amount of PVA increased.